How to Improve Worker-Firm Matching: Evidence from a Temporary Foreign Worker Market - Yoon Y. Cho; Soohyung Lee (Institute of Labor Economics (IZA), 2021)
This paper investigates the role of worker-firm matching algorithms in accounting for early job separation rates. For this purpose, we examine Koreaâ exteuro™s temporary foreign worker program in which the government classifies firms by priority levels and matches them with foreign workers based on their stated preferences. Using administrative data, we examine predictors for the job separation rates and propose alternative matching methods using the serial dictatorship. Our simulation results show that alternative matching methods can substantially reduce job separation rates, suggesting a possible improvement of the Korean program.
Keywords: J4; J6; O15; 330; market design; migration; temporary immigrants; job matching; employment permit system